Significados de consumo de lazer e o bem-estar subjetivo de mulheres lésbicas - Nóbrega, Flaviana Santos da (2021)
This research has as its central theme the subjective well-being associated with the meanings of leisure consumption. In this context, consumption is observed as hedonic, which is significant for the subjective well-being of individuals. The question of how individuals seek subjective well-being is a concern that guides this research, seeking to understand how subjective well-being is affected by leisure consumption. Thus, the general objective of the research is: to understand the meanings of leisure consumption for the pursuit of subjective well-being by lesbian women. As for the methodological path, the research has a qualitative, exploratory approach, the method was by oral history, and the research subjects were lesbian women who consume some leisure. The data were collected using the semi-structured interview instrument and narrative analysis was used to understand the answers. In the analysis and discussion of the results, three categories emerged, Life trajectory, Leisure choice and Meanings of consumption, from which the subcategories emerged. It was observed that leisure consumption is beyond an escape from routine, a moment of distraction, when associated with the meanings of consumption. However, in terms of theoretical implications, this study advances the debate by exploring the association between subjective well-being and leisure consumption meanings of lesbian women. Therefore, by bringing these themes together, the goal of understanding the perception of leisure consumption meanings and their associations with subjective well-being in an innovative consumption context was achieved. As for the social implications, this study may contribute to strengthen social marketing programs, which are willing to study and research leisure consumption meanings in a way that provides a reflection on consumption meanings and their association with subjective well-being and provides more welcoming.